Kepemimpinan Kepala Sekolah SMKS Rokita Sari 2 Bangun Purba Dalam Meningkatkan Kinerja Guru: Penelitian - Duwi Cahya; Safriza Putri Utami; Dearma Purba; Rotua Sahat P Simanullang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the leadership of the principal of SMKS Rokita Sari 2 Bangun Purba in improving teacher performance. The research method used is descriptive qualitative with data collection techniques through semi-structured interviews with the school principal. The interview questions focused on leadership vision, coaching strategies, academic supervision, motivation, and facilitation of teacher competence development. The results of the study show that the principal has a clear vision in directing teachers not only to implement the curriculum but also to prepare students for the world of work. The principal conducts regular supervision, provides simple appreciation for outstanding teachers, and supports teacher participation in training and workshops. These strategies have led to improved discipline, creativity, and professionalism among teachers. Thus, the leadership of the principal at SMKS Rokita Sari 2 Bangun Purba plays an important role in creating a conducive work environment to enhance the quality of education.